Anne Kelly Knowles (ed.), Placing History: How Maps, Spatial Data, and GIS Are Changing Historical Scholarship (Redland: ESRI Press, 2008), xx, 313pp; with a digital supplement edited by Amy Hillier. - Southall, Humphrey (International Journal of Humanities & Arts Computing: A Journal of Digital Humanities, 2009)
The article presents a review of the book "Placing History: How Maps, Spatial Data and GIS Are Changing Historical Scholarship," edited by Anne Kelly Knowles with a digital supplement edited by Amy Hillier.